The weekend effect does not influence management of inflammatory bowel disease. Issue 1 (10th June 2019) - Persaud, Alana; Patel, Pavan; Motlaghzadeh, Yasaman; Ahlawat, Sushil
Abstract : Background: The weekend effect describes worsened outcomes due to perceived inefficiency occurring over the weekend. This effect has not been studied in inflammatory bowel disease (IBD) despite increasing prevalence in the community. Therefore, our aim is to assess differences in the outcomes of weekend versus weekday management of IBD exacerbations. Methods: The National Inpatient Sample database comprises approximately 20% of admissions to nonfederal hospitals in the United States. Complications requiring hospitalization ("flares") were the criteria upon which patient selection was based. A total of 193, 848 flares were identified from 2008 to 2014 using the International Classification of Diseases 9th edition codes. Differences in time to first procedure, length of stay (LOS), and cost were evaluated for patients with flares between weekend and weekday admissions. Results: The time to first procedure was 3.33 days on weekends versus 3.19 days on weekdays ( P < 0.001). The mean LOS was shorter when admissions occurred on weekends versus weekdays (8.01 days vs 8.22 days, P < 0.001). Finally, the cost of hospitalization was higher for weekday admissions versus weekend admissions ($18 072 vs $17 495, P < 0.001). Conclusion: Our results showed a similar LOS and cost associated with the management of exacerbations on the weekend compared to weekdays. While many high‐risk conditions exhibit increased mortality and prolonged hospital course over the weekend, this phenomenon does not appear to affect IBD. These findings indicate efficient patient care on the weekend and can be utilized for logistical purposes such as resource allocation and procedure scheduling in the endoscopy suite. Abstract : The financial and psychological toll of inflammatory bowel disease (IBD) flares is quite significant; however, it is unknown whether weekend hospitalization for IBD exacerbations carry a higher hospitalization burden. Utilizing the National Inpatient Sample from 2008 to 2014, we show that there is no significant difference in mortality, cost of admission, or length of stay between weekend and weekday admissions. Given effective management on the weekends, these data can be utilized for the purposes of logistic planning, such as procedure scheduling and resource allocation.